2009
DOI: 10.1128/jcm.00853-09
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and Risk Factors for Colonization by Methicillin-Resistant Staphylococcus aureus among Adults in Community Settings in Taiwan

Abstract: In order to determine the prevalence of methicillin (meticillin)-resistant Staphylococcus aureus (MRSA) colonization among adults in community settings in Taiwan and identify its risk factors, we conducted the present study. For a 3-month period, we enrolled all adults who attended mandatory health examinations at three medical centers and signed the informed consent. Nasal swabs were taken for the isolation of S. aureus. For each MRSA isolate, we performed multilocus sequence typing, identification of the sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

19
56
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(81 citation statements)
references
References 38 publications
19
56
6
Order By: Relevance
“…In the same study, the PFGE C/SCCmec IV/PVL Ϫ clone was responsible for only 8.8% of the clinical isolates. The discrepancy of clonal distributions in clinical and colonizing isolates was also identified in other studies (6,37). The finding suggested greater virulence of the clone positive for PVL than of its sister clone negative for PVL.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…In the same study, the PFGE C/SCCmec IV/PVL Ϫ clone was responsible for only 8.8% of the clinical isolates. The discrepancy of clonal distributions in clinical and colonizing isolates was also identified in other studies (6,37). The finding suggested greater virulence of the clone positive for PVL than of its sister clone negative for PVL.…”
Section: Discussionsupporting
confidence: 59%
“…In contrast to the data from the meta-analysis, results from this study indicated a strikingly high incidence of MRSA carriage (7.8%) among healthy Taiwanese children from 2005 to 2008, with rates ranging from 6.2% to 9.5% in different geographic areas. The carriage rate in children reported here was also significantly higher than in the Taiwanese adult populations surveyed during the same period (3.8%; P Ͻ 0.0001) (37). This observation may suggest unique epidemiology for MRSA in Taiwanese children or, more likely, a universal increase in MRSA carriage in the past decade.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…This finding was unexpected and can be misleading due to the relatively small number of MRSA carriers in the current study and the fact that the MRSA strains were frequently predominantly limited clones in a defined environment (21,22). Indeed, previous molecular epidemiology studies of CA-MRSA indicated that a prevalent clone, ST59, was circulating in Taiwan and accounted for Ͼ80% of MRSA carriage isolates in both pediatric and adult populations (7,9). The majority of nasal MRSA isolates in the current study were also of the ST59 clone (equivalent to spa type t437).…”
Section: Discussionmentioning
confidence: 44%
“…In Taiwan, MRSA has accounted for Ͼ50% of childhood CA infections since 2005 (8). Carriage of MRSA in the nose was identified in 7.8% and 3.7% of the pediatric and adult populations in Taiwan, respectively (7,9). The individuals with an increased risk of MRSA carriage included very young children (2 to 6 months old), those living in a crowded environment (i.e., with greater number of siblings, attending day care), adults with household members Ͻ7 years old, or those who received antibiotic treatment in the preceding year.…”
mentioning
confidence: 99%